2012
DOI: 10.1891/0889-8391.26.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Change in Mindfulness-Based Stress Reduction: Self-Compassion and Mindfulness as Mediators of Intervention Outcomes

Abstract: Research has demonstrated support for the efficacy of mindfulness-based stress reduction (MBSR) in alleviating psychological distress and symptoms. Less is known, however, about the mechanisms through which MBSR achieves its outcomes. This study examined mindfulness and self-compassion as potential mediators of MBSR's effects on several processes and behaviors related to emotion regulation, using data from a randomized trial of MBSR versus waitlist (WL), in which MBSR participants demonstrated significantly gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 42 publications
9
87
0
1
Order By: Relevance
“…MBSR interventions were found to increase self-compassion [42; 43]. Both self-compassion and mindfulness were described as mediators of intervention effects of MBSR [20].…”
mentioning
confidence: 99%
“…MBSR interventions were found to increase self-compassion [42; 43]. Both self-compassion and mindfulness were described as mediators of intervention effects of MBSR [20].…”
mentioning
confidence: 99%
“…Practising new ways of relating to conscious experience is fundamental in mindfulness training and can include attitudinal change (e.g. curiosity, kindness and acceptance; Keng et al 2012), as well as cognitive re-orientation (e.g. distancing, de-centering and re-perceiving; Shapiro et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers' embodiment of these qualities, as well as frequent reminders in the meditation instructions to be nonjudgmental, open, and curious, is believed to help participants learn to treat themselves with more warmth and friendliness. Several studies have shown increases in selfcompassion following MBSR and MBCT (Keng et al 2012;Kuyken et al 2010). A few have shown increased empathy for others following MBSR (Birnie et al 2010;Shapiro et al 1998).…”
Section: Implicit Ethics In Mbismentioning
confidence: 99%